The miR-146a SNP Rs2910164 and miR-155 SNP rs767649 Are Risk Factors for Non-Small Cell Lung Cancer in the Iranian Population - Neda K. Dezfuli; Ian M. Adcock; Shamila D. Alipoor; Sharareh Seyfi; Babak Salimi; Maryam Mafi Golchin; Neda Dalil Roofchayee; Mohammad Varhram; Esmaeil Mortaz (Canadian Respiratory Journal)
Background. Lung cancer is one of the leading causes of death worldwide. MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression and may act as both tumor suppressors and as oncogenes. The presence of single nucleotide polymorphisms (SNPs) inside the miRNA genomic region could affect target miRNA maturation, expression, and binding to its target mRNA and contribute to cancer development. Previous studies on the SNPs Rs2910164 in miR-146a and Rs767649 in miR-155 showed association with non-small cell lung cancer (NSCLC) development. Thus, the aim of this study was to detect any correlation between those SNPs in Iranian NSCLC patients. Methods. In a small cohort study, 165 NSCLC patients and 147 noncancer controls were enrolled between Apr 2015 and Sep 2019 at the Masih Daneshvari Hospital, Tehran, Iran. Allele frequencies from the genomic DNA of blood cells were studied using PCR-RFLP and their association with the risk of lung cancer was evaluated. Results. The rs2910164C allele (OR = 1.56, 95% CI = 1.10–2.21, p=0.012) and CC genotype (OR = 2.93, 95% CI = 1.07–7.9, p=0.034, respectively) were associated with a significantly increased risk for lung cancer compared to that for the GG genotype. When patients were stratified according to smoking exposure, no association with rs2910164 variants was found. The AT genotype (OR = 0.57, 95% CI = 0.33–0.99, p=0.048) and the A allele frequency (OR = 0.58, 95% CI = 0.35–0.98, p=0.043) in rs767649 were lower in NSCLC patients in comparison with the control group. In addition, the rs767649 AT genotype frequency in smoking controls was higher than in smoking NSCLC patients (OR = 0.44, 95% CI = 0.21–0.90, p=0.024). No association was found between rs2910164 and rs767649 variants and stage or type of NSCLC. Conclusion. Our finding suggests that miR-146a rs2910164 and miR-155 rs767649 polymorphisms may be considered as genetic risk factors for the susceptibility to NSCLC in the Iranian population. However, a larger multicenter study across Iran is needed to confirm these findings.